The outcomes of concomitant catheter ablation in non-mitral valve cardiac surgery—a systematic review and meta-analysis of the literature - Wilson-Smith, Ashley R.; Wilson-Smith, Christian J.; Smith, Jemilla Strode; Ng, Dominic; Muston, Benjamin T.; Eranki, Aditya; Williams, Michael L.; Ussher, Nathan; Gupta, Aashray K. (Annals of Cardiothoracic Surgery, 2024)
Background: Atrial fibrillation (AF) is the most common form of cardiac arrythmia, with a key importance in the perioperative setting of cardiac surgery. In recent years, the question as to whether pre-existent AF should be treated concomitantly when undergoing cardiac surgery has been heatedly debated. This systematic review and meta-analysis sought to delineate the outcomes of patients undergoing concomitant AF ablation procedures alongside cardiac surgery. Methods: The methods for this systematic review and meta-analysis adhered to the Preferred Reporting Items for Systematic Reviews and Meta-analyses statement. Four databases were searched, ultimately yielding 22 papers for inclusion, using appropriate search terminology. Meta-analysis using proportions or means, as appropriate, were applied. Kaplan-Meier curves were digitized and aggregated using previously reported and validated techniques. Results: A total of 9,428 patients (67% male) were identified across the study period as having received non-mitral cardiac surgery and concomitant AF ablation procedures. On actuarial assessment, freedom from AF was found to be 93%, 88%, 85%, 82%, and 79% at 1 through to 5 years, respectively. Freedom from mortality was found to be 94%, 93%, 91%, 90%, and 87% at 1 through to 5 years, respectively. Conclusions: This review demonstrated excellent freedom from AF out to a long-term follow-up of 5 years. Freedom from mortality was also encouraging. Emerging data are increasingly illustrating that in this patient cohort, concurrent treatment of pre-existent AF with cardiac and/or valvular disease at the point of operation should be the standard of care. Robust data in the form of randomized control trials will hopefully solidify this assertion.